Ideas About Mining in Antioquia. Development, Community Governance and Collective Settings - Eslava, Adolfo; Preciado Restrepo, Andres Felipe (Sociedad y Economía, 2019)
This article addresses the conceptual discussion around the ideas on the subject of the mining industry in Antioquia. Through a qualitative approach which mixes field experience and conceptual analysis, the article is based on the mercantile and state failures to promote development and thus it aims to introduce community governance as an analytical category which allows understanding the community, its attributes and capabilities, particularly, in the context of gold mining. In short, the article presents the analytical elements that allow the connection between quotidian arrangements and public decision-making processes, namely, microfundament macro-hypotheses to reach scenarios where public policies are the result of collective action.